2021
DOI: 10.1007/s41024-021-00148-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-hazard reliability assessment of historical brick minarets

Abstract: Historical brick minarets are the main elements of Iranian architecture and exist throughout Iran in different dimensions and heights. In this paper, the structural behavior of the Gaskar brick minaret, in the north of Iran, with a height of 16.11 m, has been studied against wind and earthquake hazards. Accurate discretization of finite element (FE) model of the minaret is performed to achieve accurate structural results. Then the wind load (WL) and earthquake load demand are determined according to the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The macro modeling technique is one of the commonly used masonry structural modeling techniques in the literature. The historical masonry bell towers in South-East Lombardy in Italy [63], historical fortified masonry palaces in Switzerland and Northern Italy [64], Emir Bayındır Bridge in Turkey [65], San Pietro and San Benedetto churches in Italy [66], Torre De la Vela in Spain [67], Gaskar brick minaret in Iran [68] and five historical masonry minarets in Antalya (Turkey) [69] are some of the studies examining the seismic behavior of different types of structures using this type of structural modeling technique. While doing this type of modeling, analyses are carried out without making any distinction between the binding material (mortar, etc.)…”
Section: Structural Analysesmentioning
confidence: 99%
“…The macro modeling technique is one of the commonly used masonry structural modeling techniques in the literature. The historical masonry bell towers in South-East Lombardy in Italy [63], historical fortified masonry palaces in Switzerland and Northern Italy [64], Emir Bayındır Bridge in Turkey [65], San Pietro and San Benedetto churches in Italy [66], Torre De la Vela in Spain [67], Gaskar brick minaret in Iran [68] and five historical masonry minarets in Antalya (Turkey) [69] are some of the studies examining the seismic behavior of different types of structures using this type of structural modeling technique. While doing this type of modeling, analyses are carried out without making any distinction between the binding material (mortar, etc.)…”
Section: Structural Analysesmentioning
confidence: 99%
“…Despite requiring high computational effort, Monte Carlo simulation is an efficient method for reliability evaluation of complex engineering structures [20][21][22][23][24]. In this paper, the reliability analysis of galloping stability of the beam was performed using a large number of Monte Carlo simulations.…”
Section: Monte Carlo Simulation and Reliability Evaluationmentioning
confidence: 99%
“…The study revealed that walls significantly enhanced the seismic capacity of structures, particularly in low-rise buildings (Wijaya et al 2020). Pouraminian (2022) analyzes the structural resilience of the Gaskar brick minaret in northern Iran to wind and earthquake hazards using a finite element model. The study demonstrates that the minaret can withstand design wind loads and resists significant seismic impacts with only slight potential damage.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrates that the minaret can withstand design wind loads and resists significant seismic impacts with only slight potential damage. It highlights the importance of incorporating both wind and seismic considerations in the conservation strategies for historical structures (Pouraminian, 2022). Rahgozar et al (2021) explores the effectiveness of controlled rocking steel cores (CRSCs) in reducing damage from earthquakes.…”
Section: Introductionmentioning
confidence: 99%